Cognition of Regional Economic Growth Based on China's Intellectual Class - Liu, Ming-Yang (Frontiers in Sustainability, 2022)
To understand the cognition of China’s intellectual class on economic growth, this paper consulted the related documents and conducted questionnaires in China. The collected data is analysed by SPSS software package to establish a comprehensive framework model, which can quantitatively analyse the relationship between regional economic growth and its predictors. The relationship can be described as follows: YREG=0.201XEI+0.149XTEP+0.217XPO+0.148XTE+0.480XNR+θ or YREG=0.53XTRE+ 0.480XNR+θ. The model suggested that regional economic growth was driven predominantly by talent rooting environment and natural resources. Compared with policy orientation, the talent exchanging platform was profound to pay more attention to the future development of talent. The model also demonstrated that increased education investment plays a pivotal role in China’s intellectual class, which will directly or indirectly affect talent development, talent introduction and the environment for talents to be rooted.